Flip the Switch: The Impact of the Rural Electrification Administration 1935–1940. (16th December 2015) - Kitchens, Carl; Fishback, Price
Abstract : To isolate the impact of access to electricity on local economies, we examine the impact of the Rural Electrification Administration low-interest loans in the 1930s. The REA provided loans to cooperatives to lay distribution lines to farms and aid in wiring homes. Consequently, the number of rural farm homes electrified doubled in the United States within five years. We develop a panel data set for the 1930s and use changes within counties over time to identify the effect of the REA loans on a wide range of socio-economic measures. The REA loans contributed significantly to increases in crop output and crop productivity and helped stave off declines in overall farm output, productivity, and land values, but they had much smaller effects on nonagricultural parts of the economy. The ex-ante subsidy from the low-interest loans was large, but after the program was completed, nearly all of the loans were fully repaid, and the ultimate cost to the taxpayer was relatively low.